ISOLASI DAN IDENTIFIKASI SENYAWA ALKALOID DARI KULIT BATANG DADAP MERAH (Erythrina crista-galli) SERTA UJI AKTIVITASNYA TERHADAP ENZIM pbDHFR - MASRUTJI HANDAJANI, 080942006 (2011)
The Erythrina genus is a member of Leguminocea family contains of erythrinan skeleton alkaloids. Many types of alkaloid from Erythrina have been successfully isolated and have a potential property as antimalaria. Based on preliminary screening of alkaloid on the stembark of Erythrina crista-galli showed the presence of alkaloid using Meyer test. The objectives of this research were isolation and identification of alkaloid compound from stembark of the dadap merah (Erythrina crista-galli), determination of its in vivo antimalaria activity against P. berghei and determination of its in vitro enzyme inhibition against pbDHFR. The alkaloid was extracted using acid-base method and isolation was carried out by column chromatography technique and thin layer chromatography. Identification of alkaloid compound was carried out by 1H-NMR, 13C-NMR and IR techniques. In vivo test against P. berghei was carried out as follow: after infection with P. berghei, as many as 30 female mice were divided into six treatment groups. One group of mice was not treated by anything, five another groups were dosed by pirimethamine of 25 mg/kg body weight and by alkaloid extract of 25, 50, 75 and 100 mg/kg body weight. In vitro test against pbDHFR was carried out by treating pbDHFR with 25, 50, 75 and 100 mg/mL of alkaloid extract. Inhibition activity was measured spectrophotometrically at 340 nm. The 1H-NMR, 13C-NMR and IR data interpretation, as well as comparison with spectroscopic isolated alkaloid from the other Erythrina genus data indicated that the isolated alkaloid is considered as 8-oxo-erythraline. In vivo test against P. berghei indicated that ED50 of alkaloid extract is 88.139 mg/kg body weight. Meanwhile, inhibition test on pbDHFR enzyme showed that IC50 is 43.722g/mL.